Microchanneled ceramic membranes for oxygen separation from air - Shao, Xin (Curtin University, 2015)
This thesis describes a novel microchanneled membrane that was fabricated using a mesh-templating phase inversion process. The microchanneled membrane showed remarkable oxygen flux, good mechanical strength and thermal compatibility. Control of the fabrication parameters and the formation mechanism are discussed. Further improvement in the oxygen flux was achieved by changing materials and coating catalysts. Finally, the different mechanisms of oxygen permeation in microchanneled membranes were studied regarding gas diffusion, and contributions from the microchannel walls.